Effect of dexmedetomidine on postoperative systemic inflammation and recovery in patients undergoing digest tract cancer surgery: A meta-analysis of randomized controlled trials - Xu, Wenjie; Zheng, Yuxiang; Suo, Zizheng; Fei, Kailun; Wang, Yalong; Liu, Chao; Li, Shuai; Zhang, Mingzhu; Zhang, Yefan; Zheng, Zhaoxu; Ni, Cheng; Zheng, Hui (Frontiers in Oncology, 2022)
Perioperative immune function, postoperative cognitive function and prognosis are momentous issues for patients undergoing digestive tract cancer surgery. Studies have investigated the efficacy of dexmedetomidine (DEX) administration on these issues, but the results are inconsistent. Therefore, this meta-analysis aimed to summarize all the existing evidence and draw a conclusion more accurately on these associations. Trials were located through electronic searches of the PubMed, Embase, the Cochrane Library and Web of Science databases sources (from the establishment date of databases to April 2022). Bibliographies of the retrieved articles were checked. A total of 17 RCTs involving 1619 patients were included. The results showed that DEX decreased the level of C-reactive protein (SMD = -4.26, 95%CI: -6.16, -2.36), TNF-α (SMD = -4.22, 95%CI: -5.91, -2.54) and IL-6 (SMD = -2.71, 95%CI: -4.46, -0.97), and increased the level of IL-10 (SMD = 1.74, 95%CI: 0.25, 3.24). DEX also increased CD4+ T cells (SMD = 0.55, 95%CI: 0.29, 0.82) and CD4+/CD8+ ratio (SMD = 0.62, 95%CI: 0.24, 1.01). Thus, DEX was associated with alleviation of postoperative systemic inflammatory response and immune dysfunction. Furthermore, DEX increased mini-mental state examination scores at 12h (SMD = 1.10, 95%CI: 0.74,1.45), 24h (SMD = 0.85, 95%CI: 0.59, 1.11), 48h (SMD = 0.89, 95%CI: 0.50, 1.28) and 72h (SMD = 0.75, 95%CI: 0.38, 1.11) after surgery. DEX decreased the occurrence of postoperative cognitive dysfunction (POCD) at 24h (OR = 0.22, 95%CI: 0.11, 0.46) and 72h (OR = 0.39, 95%CI: 0.22, 0.68) after surgery. DEX decreased first flatus time (SMD = -1.55, 95%CI: -2.82, -0.27) and hospital stay (SMD = -1.23, 95%CI: -1.88, -0.59). Therefore, based on perioperative immune dysfunction alleviation, DEX attenuated POCD and potential neuroinflammation, improved postoperative recovery and clinical prognosis of patients undergoing digest tract cancer surgery. Further studies are necessary to elucidate the clinical application of DEX from an immunological perspective.